2010
DOI: 10.1371/journal.pone.0014236
|View full text |Cite
|
Sign up to set email alerts
|

A Broad Assessment of Factors Determining Culicoides imicola Abundance: Modelling the Present and Forecasting Its Future in Climate Change Scenarios

Abstract: Bluetongue (BT) is still present in Europe and the introduction of new serotypes from endemic areas in the African continent is a possible threat. Culicoides imicola remains one of the most relevant BT vectors in Spain and research on the environmental determinants driving its life cycle is key to preventing and controlling BT. Our aim was to improve our understanding of the biotic and abiotic determinants of C. imicola by modelling its present abundance, studying the spatial pattern of predicted abundance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 64 publications
6
107
1
1
Order By: Relevance
“…Indeed, in Italy at least, C. imicola would appear to be in stasis as it has shown no expansion whatsoever in its range since the year 2000, when Italy implemented its large-scale vector surveillance programme, which has been maintained continuously ever since (69). This suggests that, at some point after the last Ice Age, the distribution of C. imicola stabilised within the Mediterranean Basin, but remains fragmented and A recent modelling study (70) indirectly supported the view that C. imicola is constrained by its ecology and indicated that there is no evidence to suggest that its range in Spain will expand; nevertheless, it is expected that C. imicola will become more abundant in the future, in particular in those south-western areas where it has long been established and where, in all likelihood, it was involved in the large outbreaks of bluetongue that affected the region in the 1950s. A subsequent micro-satellite study (71), conducted on more than 20 populations of C. imicola collected from around the southern and northern shores of the Mediterranean Sea, points unequivocally to its ancient presence within the Basin and suggests that there is longitudinal and ongoing gene flow between the North African and Central Mediterranean populations.…”
Section: Climatic Factors and Culicoidesmentioning
confidence: 99%
“…Indeed, in Italy at least, C. imicola would appear to be in stasis as it has shown no expansion whatsoever in its range since the year 2000, when Italy implemented its large-scale vector surveillance programme, which has been maintained continuously ever since (69). This suggests that, at some point after the last Ice Age, the distribution of C. imicola stabilised within the Mediterranean Basin, but remains fragmented and A recent modelling study (70) indirectly supported the view that C. imicola is constrained by its ecology and indicated that there is no evidence to suggest that its range in Spain will expand; nevertheless, it is expected that C. imicola will become more abundant in the future, in particular in those south-western areas where it has long been established and where, in all likelihood, it was involved in the large outbreaks of bluetongue that affected the region in the 1950s. A subsequent micro-satellite study (71), conducted on more than 20 populations of C. imicola collected from around the southern and northern shores of the Mediterranean Sea, points unequivocally to its ancient presence within the Basin and suggests that there is longitudinal and ongoing gene flow between the North African and Central Mediterranean populations.…”
Section: Climatic Factors and Culicoidesmentioning
confidence: 99%
“…This dependency on air temperature was confirmed in several C. imicola modelling studies using climatic data. Purse et al [18] found C. imicola in the Mediterranean Basin to occur in warm (annual mean [12][13][14][15][16][17][18][19][20] • C) regions with low seasonal variations. A model developed by…”
Section: Culicoides Life Cyclementioning
confidence: 99%
“…Conte et al [11] added the presence of water in rivers to meteorological and topographic data for a model for Italy based on 546 trapping sites, resulting in 75% correctly classified sites in an internal validation. Acevedo et al [12] included the availability of host species, as well as land cover, climatic and pedological variables, in an analysis based on trappings during the period [2005][2006][2007][2008] in Spain.…”
mentioning
confidence: 99%
“…Así, la estimación de la abundancia de una especie en todo su área de distribución es un proceso clave para poder comprender el ciclo epidemiológico de los patóge-nos en los que dicha especie juega un papel relevante bien como vector u hospedador. Por ejemplo, la abundancia de ciervo (Cervus elaphus), estimada mediante SDM, ha sido recientemente utilizada para estudiar el papel que ésta juega en la abundancia del principal vector del virus de la lengua azul (Culicoides imicola) en la Península Ibérica (Acevedo et al, 2010c). Desde el punto de vista de la sanidad animal es necesario también conocer la abundancia de las poblaciones para poder establecer planes de contingencia frente a la entrada de un patógeno en el territorio como los que actualmente están emergiendo en la Península Ibérica (Ruiz-Fons et al, 2008).…”
Section: Abundancia Relativaunclassified